OSIĄGNIĘCIA POLSKICH ROMANISTÓW W CIĄGU OSTATNICH DWÓCH LAT (2006/2007 – 2007/2008) - Zabłocka, Maria (Zeszyty Prawnicze, 2017)
Polish Romanistic Research in the Last Two Years (2006/2007 – 2007/2008) Summary The article presents publications of Polish romanists published in the last two academic years. They include editions of the sources, their translations accompanied by commentaries, as well studies on Roman private law covering the law of persons, family law, law of property, succession, obligations and procedure. An important part of the recent studies is devoted to public law: above all criminal law and broadly understood administrative law. Several authors addressed the problem of the influence of Roman law on the legal culture of Europe. Research was done as well on the history of law faculties and the romanists who lectured there. All these studies indicate a slight change in the scientific interest of the Polish romanists. We welcome the fact that more interest was paid to various problems of public law, in this way the romanistic research may be able to show the roots of the later and modern jurisprudence. One could postulate further studies not on the classical period of Roman law but also on its later developments. Scholars should never limit themselves to study of subjects reflecting contemporary legal science, as we never know if the one day the ‘dated’ institutions should not revive in a slightly changed form: such is the case of the modern construction of transfer of ownership as a security for debt functionally reflecting the Roman fiducia cum creditore contracta. In this manner the analysis of the ancient legal structures may provide for better understanding of the presently binding norms.